1996
DOI: 10.1523/jneurosci.16-05-01808.1996
|View full text |Cite
|
Sign up to set email alerts
|

GABA stimulates chemotaxis and chemokinesis of embryonic cortical neurons via calcium-dependent mechanisms

Abstract: During rat cortical development, when neurons migrate from the ventricular zone to the cortical plate, GABA localizes within the target destinations of migratory neurons. At this time, cells in germinal zones and along migratory pathways express GABA receptor subunit transcripts, implying that in vivo, GABA may be a chemoattractant. We used an in vitro strategy to study putative chemotropic effects of GABA on embryonic rat cortical cells. GABA stimulated neuronal migration in vitro at embryonic day 15 (E15). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
289
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(300 citation statements)
references
References 43 publications
10
289
0
1
Order By: Relevance
“…In neutrophils, disassembly of the microtubule network has been shown to induce development of polarity, a key feature required for chemokinesis and chemotaxis (24). Recent studies have suggested a role for the GABA B R in directed migration of embryonic cortical neuron, and motility of spinal neuroblasts, thus supporting the concept that these receptors can guide directed migration or growth (25). The present study shows that GABA B R selectively induces neutrophil chemotaxis via an Akt-dependent mechanism because pretreatment with LY294003 or simultaneous addition of CGP52432 inhibited baclofen-stimulated neutrophil chemotaxis.…”
Section: Discussionmentioning
confidence: 96%
“…In neutrophils, disassembly of the microtubule network has been shown to induce development of polarity, a key feature required for chemokinesis and chemotaxis (24). Recent studies have suggested a role for the GABA B R in directed migration of embryonic cortical neuron, and motility of spinal neuroblasts, thus supporting the concept that these receptors can guide directed migration or growth (25). The present study shows that GABA B R selectively induces neutrophil chemotaxis via an Akt-dependent mechanism because pretreatment with LY294003 or simultaneous addition of CGP52432 inhibited baclofen-stimulated neutrophil chemotaxis.…”
Section: Discussionmentioning
confidence: 96%
“…Our hypothesis was based on the previous findings that Ca 2ϩ signaling influences the mitosis of neuronal progenitors and their nuclear interkinetic translocation in the embryonic retina (21), and that [Ca 2ϩ ] fluctuations also affect cellular migration in cerebellar granular cells (22)(23)(24), cultured neuronal progenitors (25), and postmitotic cortical neurons (26). Spontaneous Ca 2ϩ transients or Ca 2ϩ waves are visible in both the VZ and SVZ and increase in intensity during corticogenesis (27,28), suggesting their involvement in neuronal proliferation and migration.…”
mentioning
confidence: 99%
“…Baclofen did not produce detectable changes in either membrane potential or Ca 2ϩ c (data not shown), implying either that the function of GABA B receptor/ Ca 2ϩ channels might have been compromised during acute cell preparation or that the activation of these receptors nominally contributes to membrane potential or Ca 2ϩ c at this stage of cortical neuron development. Relatively modest contributions of GABA B receptor/Ca 2ϩ channels to Ca 2ϩ c levels were indeed shown in cell cultures of migrating and differentiating cortical neurons after recovery from dissociation (see Behar et al, 1996) (see Fig. 9B).…”
Section: Functional Responses To Gaba Increase During Neuronal Differmentioning
confidence: 69%
“…Functional GABA B receptors have been shown previously to mediate cortical neuronal migration from the VZ/SVZ to the CP/SP in rat neocortex over E17-E19 (Behar et al, 1996(Behar et al, , 1998(Behar et al, , 2000.…”
Section: Gaba a Receptor Subunit Expressions Change With Neuronal Linmentioning
confidence: 95%
See 1 more Smart Citation